Potencial de leveduras no controle de Phytophthora sojae - Saab, Mariana Ferreira (2014)
Brazil is the second largest producer and exporter of soybeans, meal and oil in the world, ensuring the country a role of great potential for the product. The soybean crop is attacked by various diseases caused by fungi, bacteria and viruses which burdens the cost of production by the need to adopt measures of preventive and curative control throughout cycle. Among the diseases of Phytophtora root rot caused by Phytophthora sojae, is considered one of the most destructive for causing death of plants in all stages of development. The use of resistant cultivars is the primary measure of control, since there is no chemical control for the specific pathogen. Thus, alternative control Phytophtora presents itself as an important aspect of research, which can bundle other measures of protecting plants against diseases, such as biological control and resistance induction. The objective of this study was to evaluate the potential of yeasts in controlling P. sojae. In vitro, evaluated the inhibition zone formed between pathogen and antagonist in pairing colonies and production of volatile compounds in divided plates. In vivo, induction of resistance was assessed by the activity of peroxidase, catalase, polyphenol oxidase, phenylalanine ammonia lyase and lipoxygenase, after treatment with yeast-like fungi and pathogen inoculation in soybean . We also evaluated the production of phytoalexins in soybean cotyledons and hypocotyls of bean. Disease severity was estimated by lesion length 72 and 120h after pathogen inoculation. In the confrontation between pathogen and antagonist yeast four highlighted by the formation of inhibition zone Debaryomyces etchellsii, Saccharomyces cerevisiae 2, Pichia sp. and an isolated yeast raisin (DRD1). We detected a significant increase in the activity of peroxidase in treatments D. etchellsii, S. cerevisiae 2, EM 21.1 , Hanseniaspora opuntiae 2, potato dextrose (BD) and Pichia sp . 2 precipitate. For polyphenoloxidase the best treatments were D. etchellsii, S. cerevisiae 2, EM 21.1, H. opuntiae 2, Pichia sp. 2 and BD, only the first hours of review. The production of glyceollin in soybean cotyledons was significantly higher in treatments H. opuntiae 1, S. cerevisiae 1, S. cerevisiae 2, EM 21.1, H. opuntiae 2, Pichia sp. 2, DRD1 , and saprobic (CUI) , when compared with the control (water). To phaseolin produced in bean hypocotyls, Pichia sp. was the only treatment that overcame and statistically different from the control. The yeasts showed no efficiency to reduce disease severity.